2020
DOI: 10.1088/1361-6463/abb26f
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetocaloric effect in LiLnP4O12 (Ln = Gd, Tb, Dy) single crystals

Abstract: We have studied the magnetic and magnetocaloric (MC) properties of lithium lanthanide tetraphosphates LiLnP4O12 (Ln = Gd, Tb, Dy) single crystals (SCs) upon the magnetization (M) and heat-capacity (Cp) measurements. Detailed investigations in the temperature range T = 2–300 K indicate that all SCs exhibit paramagnetic (PM) character with effective PM moments close to those expected for free Ln 3+ ions. The magnetic contribution to Cp takes place strongly at temperatures below 20 K that enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…At the lowest possible temperature, the ideal MC material should have a degenerate paramagnetic state, that is, there is no coupling between the magnetic moments. The coupling between the magnetic moments is normally correlated to the distance between RE 3+ ions, which leads to magnetic ordering at the Neel or Curie temperature . For Li 3 K 9 Gd 3 (BO 3 ) 7 , the Gd···Gd separations within the zigzag [Gd–O] ∞ chains are 4.8767 Å for Gd(2)···Gd(2) and 5.2875 Å for Gd(2)···Gd(1), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the lowest possible temperature, the ideal MC material should have a degenerate paramagnetic state, that is, there is no coupling between the magnetic moments. The coupling between the magnetic moments is normally correlated to the distance between RE 3+ ions, which leads to magnetic ordering at the Neel or Curie temperature . For Li 3 K 9 Gd 3 (BO 3 ) 7 , the Gd···Gd separations within the zigzag [Gd–O] ∞ chains are 4.8767 Å for Gd(2)···Gd(2) and 5.2875 Å for Gd(2)···Gd(1), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The coupling between the magnetic moments is normally correlated to the distance between RE 3+ ions, which leads to magnetic ordering at the Neel or Curie temperature. 8 For Li GdVO 4 (3.93 Å), 39 and GdPO 4 (4.03 Å), 40 which is obviously beneficial to generating a large magnetocaloric effect. Magnetic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Together with the 3D framework, a large nearest Re-Re distance (∼5.6 Å 31,33 ) is thought to obstruct exchange interactions between Re ions, leading to a large MC effect of LiRe(PO 3 ) 4 at low temperatures. Investigating LiRe(PO 3 ) 4 materials with Re = Gd, Tb, Dy and Pr, Petrov et al 27,32 found their jDS m j and DT ad values at 2 K are about 9.8-27.6 J kg −1 K −1 for the eld H = 50 kOe and 3-13 K for H = 20 kOe, respectively.…”
Section: Introductionmentioning
confidence: 99%